Um retrato da trajetória de vida de professores egressos das camadas populares à luz do pensamento complexo - Horvath, Wilson Agnaldo (2017)
This research presents an analysis of the trajectory of four professors with a Master´s degree from the Brazilian popular strata that teach at two private universities in the city of São Paulo. The objective of the study was to understand how these subjects managed to re-significate the oppressive elements present in their life histories, especially in childhood and youth, and transcend a cruel and merciless reality, becoming university professors. The methodological procedure used in the interviews was the oral history and narratives were assessed by two main concepts present in the Complex Thought written by Edgar Morin, the Cultural Imprinting and Action Ecology. The results confirm culture as constitutive and intrinsic part of human nature. The individual is marked by the social and cultural context in which he lives. The subjects of research were crossed by modernity, capitalism and its ills, by the slave-like and violent past of Brazilian historiography and patriarchalism. Nonetheless, they have managed, nevertheless, to advance and grow personally and professionally. It is concluded that, although there is a strong conditioning of the cultural elements, over determination can be subverted, since there is always the opening for chance, for the imponderable, for the new, allowing the subjects to resize their lives and transpose situations from disrepute, dishonor and debasement towards success and achievement of goals and purposes.